2015
DOI: 10.1002/jhbp.215
|View full text |Cite
|
Sign up to set email alerts
|

Can we expand the indications for laparoscopic liver resection? A systematic review and meta-analysis of laparoscopic liver resection for patients with hepatocellular carcinoma and chronic liver disease

Abstract: Liver resection (LR) for patients with hepatocellular carcinoma (HCC) and chronic liver disease (CLD) poses a high risk of serious postoperative complications and multicentric metachronous lesions requiring repeated treatment. The efficacy of laparoscopic LR (LLR) for such patients has yet to be established. The objective of this study is to test the outcomes of LLR for HCC with the aim of considering potential expansion of the indications for LLR. We performed a systematic review of the pertinent English-lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
91
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 155 publications
(103 citation statements)
references
References 60 publications
9
91
1
2
Order By: Relevance
“…These expert technical recommendations will never be confirmed by level 1 evidence, but still need to be shared so that beginners can benefit from expert guidance. Another major achievement of the consensus conferences is the publication activities related to the conferences and the systematic reviews prepared to develop recommendations before the Morioka Consensus Conference 46, 67, 84, 118, 119, 120, 121, 122. We hope that all these publications will contribute to the safe uptake of LLR.…”
Section: The Two Consensus Conferencesmentioning
confidence: 98%
See 1 more Smart Citation
“…These expert technical recommendations will never be confirmed by level 1 evidence, but still need to be shared so that beginners can benefit from expert guidance. Another major achievement of the consensus conferences is the publication activities related to the conferences and the systematic reviews prepared to develop recommendations before the Morioka Consensus Conference 46, 67, 84, 118, 119, 120, 121, 122. We hope that all these publications will contribute to the safe uptake of LLR.…”
Section: The Two Consensus Conferencesmentioning
confidence: 98%
“…In general, HCC, which is often accompanied by cirrhosis, has a high risk of postoperative complications such as ascites and liver failure 83. A meta‐analysis comparing the outcomes of LLR and OLR for HCC in patients with chronic liver disease reported favorable short‐term outcomes in the LLR group,84 which suggests that LLR results in fewer postoperative complications owing to factors such as less bleeding, a simpler mobilization procedure, and minimal destruction of the body wall 48. Furthermore, anatomical resection is preferred when performing curative resection for HCC in patients with good functional liver reserve 85.…”
Section: Indications and Oncological Outcomesmentioning
confidence: 99%
“…In addition, the incidences of postoperative ascites and liver failure are reduced with LLR for HCC (43). Pure laparoscopic hepatectomy results in minimal postoperative ascites production, which leads to a lower risk of disturbance in water and/or electrolyte balance and hypoproteinemia.…”
Section: Laparoscopic Advantages and Future Perspectivesmentioning
confidence: 99%
“…[4] LLR has recently become widely accepted as a less invasive treatment for liver tumors with specific advantages such as less intraoperative bleeding and a shorter postoperative length of hospital stay (LOS). [5,6] Partial resection (PR) of the anterolateral segments is currently considered a standard procedure. [5] Few reports have described intended laparoscopic treatments for gallbladder carcinoma (GBC); [7][8][9] however, many studies of occult GBC revealed high incidences of port site recurrence and peritoneal dissemination after laparoscopic cholecystectomy.…”
Section: Introductionmentioning
confidence: 99%